Harvest : an abstract animated short. - Goh, Vincent Zhengyang. (2010)
“Harvest” is an abstract short animation film which depicts the unintended consequences of intensive mass production system where the beings and the workers were being abused. During the age of industrialization where assembly line system had accomplished in producing a lot of products on a small amount of land at a very affordable price. It had achieved tremendous economies growth. This achievement has reshaped the whole industry’s model of production, processing and marketing of the product. In every critical event, it reshapes human’s thought and culture. The main objective of this animation is to create an awareness of the production system dedicated to the single virtue of efficiency which causes the industry to ignore the health and safety condition of the workers and the beings.